Dashboard4Dashboards; Dashboard For The Monitoring Of Dashboards And Usage Analytics - Md Zulkifli, Nurul Zahidah (IRC, 2019)
Dashboard is a tool that allows the alignment of business processes and implementation of strategies. Dashboard are more than a collection of indicators and graphics, they are found in different forms and interfaces. Before creating a dashboard, the enterprise has to identify the need for the dashboard. Due to the development of information technology, every business has a lot of data which magnify the difficulties of selecting the most relevant. With the help of dashboard, the data can be compared, and important data can be selected and visualize to help in decision making process. One of the objectives for this project is to develop a dashboard for Schlumberger that consolidate and allows monitoring of all dashboards usage. Not only that, the objective of this project also is to enable analytics on dashboard deployment and usage. The author used Power BI to develop the dashboard, a business analytics solution that enables visualization of data and sharing of insights across organization. It enables as well embedding of dashboard in mobile or website platform. The author also used R language to perform the analytics. An architecture diagram for the system as well as the detailed project planning required is included in this report.